Energy Storage - Huggins, Robert (Springer US : Imprint: Springer, 2010)
Energy Storage discusses the underlying fundamentals of all the major energy storage methods. These include the storage of energy as heat, in phase transitions and reversible chemical reactions, and in organic fuels and hydrogen, an important energy carrier. The principles involved in the storage of energy in mechanical, electrostatic and magnetic systems are also treated in some detail. Major attention is given to an up-to-date discussion of electrochemical storage systems in a way that does not require prior understanding of electrochemistry. This includes both traditional battery systems and recent developments, with special attention given to the very important, and rapidly evolving, lithium batteries. Energy Storage provides a comprehensive overview of the concepts, principles and practice of energy storage that will be useful to both students and researchers.